Perceived Ethical Leadership and Job Involvement in the Economy-specific Context - Žemgulienė Jolanta (Organizations and Markets in Emerging Economies, 2013)
The aim of this study is to examine the relationship between the supervisor’s perceived ethical behavior and work involvement in the context of different economic conditions – those of developed countries and the emerging market economies of the European Union. Economy-specific impact on the perceived ethical behavior of leaders and job involvement as its resultant attitude toward work was assessed by structural equation modeling of the data drawn from the populations of emerging market economies of Central and Eastern Europe and the developed economies of Western Europe. The data for the analysis were drawn from a large-scale European Values Study. Two samples used for the analysis consist of 899 supervisors from four developed economy European countries and 709 supervisors from four emerging economy countries of Central and Eastern Europe. The results provide empirical evidence that economy-specific context impacts the leaders’ perceived ethical behavior and its relationship with the attitude to job involvement.